The historical aspects of social care in Lithuania - Račkelienė, Aldona (Socialinė teorija, empirija, politika ir praktika, 2006)
The development of social care and common actions of Church, society and state in order to solve social problems are presented in the paper. The author describes the history of social care in Lithuania from its beginning until 1940. The beginning of social care in Lithuania is XVI century. The first social care organisations were initiated by monkhood. The elite, clergy and enlighten members of society established infirmaries and friendly societies. The education of children was organised in catholic tradition until the country was occupied by Russia. During the period of occupation, the institutions of childcare implemented the interests of Russia’s state. After the end of Lithuanian press ban, there was the increase in the number of friendly societies. The associations of organisations were established. The most famous were The Lithuanian Association of Mothers and Children Care Organisations and The Lithuanian Friendly Society of Catholic Women. Later the Union of Caritas joined the mentioned ones. In the fourth decade of XX century, there were initiatives to establish the school of social work and start the training of professional social workers.
Keywords: Social care; History; Lithuania